Seismic Retrofit of a Multispan Prestressed Concrete Girder Bridge with Friction Pendulum Devices - Alberto Maria Avossa; Danilo Di Giacinto; Pasquale Malangone; Fabio Rizzo (Shock and Vibration)
The paper deals with the proposal and application of a procedure for the seismic retrofit of an existing multispan prestressed concrete girder bridge defined explicitly for the use of friction pendulum devices as an isolation system placed between piers top and deck. First, the outcomes of the seismic risk assessment of the existing bridge, performed using an incremental noniterative Nonlinear Static Procedure, based on the Capacity Spectrum Method as well as the Inelastic Demand Response Spectra, are described and discussed. Then, a specific multilevel design process, based on a proper application of the hierarchy of strength considerations and the Direct Displacement-Based Design approach, is adopted to dimension the FPD devices. Furthermore, to assess the impact of the FPD nonlinear behaviour on the bridge seismic response, a device model that reproduces the variation of the normal force and friction coefficient, the bidirectional coupling, and the large deformation effects during nonlinear dynamic analyses was used. Finally, the paper examines the effects of the FPD modelling parameters on the behaviour of the retrofitted bridge and assesses its seismic response with the results pointing out the efficiency of the adopted seismic retrofit solution.